2019
DOI: 10.1080/09506608.2018.1564545
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of chalcogenide glass-formers

Abstract: Chalcogenide glass-formers are being used in a remarkable range of various optoelectronic, photonics, photoconducting, sensing and memory device applications. The knowledge of viscosity is essential for the processing of any glass-forming material, in particular for the fabrication of precise optical elements, which is the main application field of chalcogenide glasses. This work presents an extensive collection of all available viscosity data for chalcogenides, including the measurement methods. The Mauro-Yue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 178 publications
0
20
0
Order By: Relevance
“…The long-range diffusion/viscous flow, ≳ 1000 K, shows a much higher activation barrier, ≈1.2 eV, comparable with that found in macroscopic viscosity measurements. 91,92 The observed difference is well illustrated by two snapshots of the FPMD simulation boxes taken at 300 K and 1300 K, the insets in Fig. 12(e).…”
Section: Accepted Manuscriptmentioning
confidence: 72%
“…The long-range diffusion/viscous flow, ≳ 1000 K, shows a much higher activation barrier, ≈1.2 eV, comparable with that found in macroscopic viscosity measurements. 91,92 The observed difference is well illustrated by two snapshots of the FPMD simulation boxes taken at 300 K and 1300 K, the insets in Fig. 12(e).…”
Section: Accepted Manuscriptmentioning
confidence: 72%
“…The current idea on the 1D liquids may be extended to 0D and 2D materials. For instance, it has been demonstrated that small molecules, e.g., orthoterphenyl, are fragile with m % 80, [6,7,10,14,16] but the character may be affected by intramolecular relaxations. Are elemental van der Waals fluids such as Ar also fragile?…”
Section: Discussionmentioning
confidence: 99%
“…In brief, related backgrounds can be summarized as follows: It is known that η ( T ) in (supercooled) liquids leading to the glass transition can be approximated using the Vogel–Fulcher–Tammann (VFT) equationη(T)=ηexp{ B/(TT0) }where η ∞ (=10 −4 P = 10 −5 Pa s) is an empirically chosen viscosity at sufficiently high temperatures, B represents an activation temperature, and T 0 is referred to as the Vogel temperature, which appears to be nearly equal to the Kauzmann temperature T K . In Equation , if T 0 = 0, it reduces to the Arrhenius type, an approximate form appearing in the so‐called “strong” liquid such as SiO 2 .…”
Section: Fundamentalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, according to our opinion and experiences, this is the reasonable way to extrapolate viscosity data if melt viscosities are unknown. The different viscosity equations were tested in our work submitted for publishing [39]. Well-described chalcogenide amorphous materials (As2S3, As2Se3, Se) with measured viscosities in melt region were fitted by VFT [40][41][42] (Vogel-Fulcher-Tammann), MYEGA [43] (Mauro-Yue-Ellison-Gupta-Allan) and Ojovan [44] equations.…”
Section: Temperature Dependence Of Viscositymentioning
confidence: 99%